Effect of MAP3K8 on Prognosis and Tumor-Related Inflammation in Renal Clear Cell Carcinoma - Hao, Jiatao; Cao, Yumeng; Yu, Hui; Zong, Lu; An, Ruifang; Xue, Yan (Frontiers in Genetics, 2021)
Background: MAPK kinase kinase 8 (MAP3K8) is involved in the regulation of MAPK cascades and immune responses. Differential expression of MAP3K8 is closely correlated with tumorigenesis. In this study, we used bioinformatics tools to explore expression level, prognostic values, and interactive networks of MAP3K8 in renal clear cell carcinoma (ccRCC). Methods: Differential expression of MAP3K8 was determined by TIMER2.0, UALCAN, and Oncomine Platform. For exploration of MAP3K8 mutation profile, TIMER2.0, DriverDBv3, and cBioPortal were used. The survival module of GEPIA, UALCAN, and DriverDBv3 was used to examine the prognostic value of MAP3K8. Immune infiltration was estimated by TIMER, TIDE, CIBERSORT, CIBERSORT-ABS, QUANTISEQ, XCELL, MCPCOUNTER and EPIC algorithms. PPI networks and functional enrichment analysis were constructed using GeneMANIA, Cytoscape, and Metascape. The co-expression module in cBioPortal was used to find genes that are correlated with MAP3K8 in mRNA expression. Results: Compared to normal renal samples, ccRCC (3.08-fold change, P=1.50E-7; 1.10-fold change, P=3.00E-3), papillary RCC (2.24-fold change, P=1.86E-4), and hereditary ccRCC (1.98-fold change, P=1.69E-9) have significantly higher levels of MAP3K8 expression. Compared to Grade 1 ccRCC samples, Grade 2 (P=1.28E-3) and Grade 3 (P=7.41E-4) cases have higher levels of MAP3K8 methylation. Percentage of patients harboring MAP3K8 mutation is 0.3% from TIMER2.0 and 0.2% to 11.5% from cBioPortal. High levels of MAP3K8 expression were associated with poorer overall survival (OS) in ccRCC (GEPIA: Log-rank P=0.60E-2, HR=1.5; DriverDBv3: Log-rank P=1.68E-7, HR=2.21; UALCAN: P=0.20E-2). MAP3K8 was positively correlated with the presence of T cell regulatory (Tregs) (QUANTISEQ: Rho=0.33, P=1.59E-13). PPI network and functional enrichment analyses revealed that MAP3K8 correlated with NFKBIZ, MIAT, PARP15, CHFR, MKNK1, and ERMN, which was mainly involved in I-kappaB kinase/NF-kappaB and toll-like receptor signaling pathways. Conclusions: MAP3K8 overexpression was correlated with damaged survival in ccRC and may play a crucial role in cancer-related inflammation via I-kappaB kinase/NF-kappaB and toll-like receptor signaling pathways.